Hydroponic Assembly Training for Teachers and Senior High School Students in Kuantan Singingi - Seprido, Seprido; Desta Andriani; A. Haitami; Elfi Indrawanis; Chairil Ezward; Gusti Marlina; Wahyudi; Tri Nopsagiarti (Universitas Lancang Kuning, 2023)
Education is a very important need in society’s life. High school students and equivalent teachers are educational people who continuously learn. Hydroponics is a technology in the agricultural sector that can be adopted in the education sector. A total of 68 participants attended this hydroponics training activity, 22 were teachers and 46 were senior high schools student. All participants showed quite high enthusiasm in this training activity as shown by the high frequency of questions from all participants.